Some analytical aspects of the intermediation of oil surpluses by the eurocurrency market - MAYER, H. (PSL Quarterly Review, 2013)
The article looks at the combined current-account deficit of the oil-importing countries and of the contribution of the Euro-currency market towards financing it, exploring the economic implications of the Euro-currency market’s potential intermediary role. The analysis focuses on credit and the money supply, the question of multiplier relationships, international liquidity and the problems for domestic and international monetary stability. Comparisons are made both between the present situation and the situation existing before the oil price increase and between alternative ways of financing the deficit. JEL: E44, E51, F32, Q40